Delays in Renewal of Labor Contracts: Theory and Evidence - Danziger, Leif; Neuman, Shoshana (Journal of Labor Economics, 2005)
In many countries, an expired labor contract is automatically extended during the often‐protracted delay before the new contract is signed. Our theoretical model focuses on macroeconomic factors in explaining the delay. It emphasizes the importance of the realized nominal and real shocks, and of the levels of nominal and real uncertainty. The model is tested using Israeli collective wage agreements where long delays are frequent. The empirical findings strongly support the theoretical model. Thus, nominal uncertainty is found to increase the delay, and real uncertainty to decrease the delay, but less in the public than in the private sector.